Efficacy of tamsulosin versus tamsulosin plus lithorex-B as medical expulsive therapy following extracorporeal shock-wave lithotripsy of renal and upper ureteric stones; a randomized clinical trial - Sadrollah Mehrabi; Leila Manzouri; Asieh Kohzadi; Farhad Mehrabi (Society of Diabetic Nephropathy Prevention, 2017)
Introduction: Urolithiasis is one of the most common disorders of urinary system. Objectives: To compare the efficacy and safety of tamsulosin versus tamsulosin plus lithorex-B. Patients and Methods: This study was an open-label, randomized, controlled trial conducted in Yasuj University of Medical Sciences, Iran in 2014 to 2015. After taking informed consent, a total of 64 patients aged 18 years and over, presenting with renal or upper ureteral stones up to 20 mm in diameter were enrolled in this study. After extracorporeal shock-wave lithotripsy (SWL), patients were randomly assigned to group A (n = 32) received tamsulosin 0.4 mg and group B (n = 32) received tamsulosin 0.4 mg plus lithorex-B 400 mg orally at bed time daily for 2 weeks. Finally, patients were assessed by KUB and sonography. The stone passage rate, drug adverse effects and pain score were evaluated. All data were analyzed using SPSS 21. Results: There were no significant differences between group A and B regarding stone expulsion rates (40.6% vs 43.7%, P = 0.83), adverse effects (34.4% vs 40.6%, P = 0.79) and mean score of pain (4.31 ± 2.02 vs 5 ± 2.01, P = 0.17) after 2 weeks follow up. Primary stone size was the predicting factor of stone passage (β = -0.42, P = 0.005, Exp (β) = 0.65, CI 95%, Exp (β): 0.48-0.88). Conclusion: Tamsulosin plus lithorex-B is safe and well tolerated with no extra benefit regarding the expulsion rate in 2 weeks follow up. Hence, the necessity of conducting a trial with a longer follow up period providing comparison between tamsulosin and lithorex-B in separate group is felt.